Long Non-coding RNA X-Inactive Specific Transcript Mediates Cell Proliferation and Intrusion by Modulating the miR-497/Bcl-w Axis in Extranodal Natural Killer/T-cell Lymphoma - Liu, Qinhua; Ran, Ruonan; Wu, Zhengsheng; Li, Xiaodan; Zeng, Qingshu; Xia, Ruixiang; Wang, Yalei (Frontiers in Cell and Developmental Biology, 2020)
The present study was directed toward laying new findings for Extranodal natural killer/T-cell lymphoma (ENKL)-oriented therapy with a focus on long non-coding RNA (lncRNA)–microRNAs (miRNAs)–mRNA interaction. The expression and function of XIST (X-inactive specific transcript) were analyzed both in vivo and in vitro. The online database of lncRNA-miRNA interaction was used to screen the target of XIST, and miR-497 was selected. Next, the predicted binding between XIST and miR-497, and the dynamic effect of XIST and miR-497 on downstream Bcl-w was evaluated. We found that XIST dramatically increased in the blood of ENKL patients and cell lines. XIST knockdown suppressed the cell proliferation and migration in vivo and in vitro. Herein, we confirmed the negative interaction between XIST and miR-497. Moreover, XIST knockdown reduced the protein levels of Bcl-w, a downstream target of miR-497. XIST sponges miR-497 to promote Bcl-w expression, and finally modulating ENKL cell proliferation and migration. To be interested, inhibition of Bcl-w by ABT737 can overcome the high expression of XIST, and suppressed the ENKL proliferation and migration by inducing apoptosis. This study provided a novel experimental basis for ENKL-oriented therapy with a focus on the lncRNA–miRNA–mRNA interaction.